Book of Abstracts / International Scientific Conference »Research and Education in Nursing«, June 7th, 2018, Maribor, Slovenia: 7. junij 2018, Maribor, Slovenija - Marina Bajić; Pajnkihar, Majda; Čuček Trifkovič, Klavdija; Šoštar Turk, Sonja; Štiglic, Gregor (2018)
Along with the 25th anniversary of the establishment of the Faculty of Health Sciences, we organize the scientific conference entitled » Research and Education in Nursing Care« that will take place under the sponsorship of the president of the Republic of Slovenia, Borut Pahor. The conference's purpose and aim is to present the progress in the field of research for practice and education support, to introduce an  interdisciplinary and interprofessional approach in nursing care and health care in Slovenia and abroad and also to show the contribution of core knowledge development. The added value of the conference is the integration of higher education teachers, higher education collaborators and students with the exchange of research findings, models of good practice and innovative ideas. We will present articles from current scientific-research projects, dealing with an effective, safe, humane, patient-friendly and family-directed healthcare treatment.
Keywords: Research; Education; Nursing; Health Sciences; conference